Chemical Expansion Due to Hydration of Proton‐Conducting Perovskite Oxide Ceramics. Issue 8 (30th May 2014) - Andersson, Annika K. E.; Selbach, Sverre M.; Knee, Christopher S.; Grande, Tor; Menon, M.
<x xml:space="preserve">Abstract</x> The crystal structures of proton‐conducting BaZr1−xYxO3−x/2 (BZY05–BZY20) and BaCe0.8Y0.2O2.9 (BCY20) during hydration/dehydration has been studied by in situ high‐temperature X‐ray diffraction and thermal analysis. A contraction/expansion of the crystal lattice associated with dehydration/hydration was observed for all materials at elevated temperatures and the polymorphic phase transition temperatures of BaCe0.8Y0.2O2.9 were depressed by lowering the vapor pressure of water. A thermodynamic formalism is introduced to describe the chemical expansion associated with the hydration of oxygen vacancies in acceptor‐doped oxides. A conventional point defect model was applied to describe the lattice strain associated with the hydration. The chemical expansion is discussed with respect to the available volumetric data on the hydration of proton‐conducting oxide materials and its likely impact on ceramic fuel cells/hydrogen separation membranes utilizing a proton‐conducting electrolyte.